Tropenmedizin im Zeitalter hoher globaler Mobilität: Schistosomiasis bei einer Schulklasse nach Ruandareise - Mickan, Christina; Junghanss, Thomas; Stojković, Marija (Deutsche medizinische Wochenschrift, 2019)
Introduction Schistosomiasis is one of the most common parasitic diseases worldwide. If left untreated, intestinal (Schistosoma mansoni, S. japonicum, S. mekongi) and urogenital (S. haematobium) chronic disease manifestations occur depending on the parasite load. The early phase however is characterized by fever and an immune-complex-mediated illness. Long-distance travel to tropical regions is on the rise, academic partnerships and humanitarian missions take even young people to developing countries.